Effect of N-doped carbon quantum dots/multiwall-carbon nanotube composite support on Pt catalytic performance for methanol electrooxidation. Issue 71 (14th July 2016) - Zhang, Jing-Jia; Sui, Xu-Lei; Zhao, Lei; Zhang, Li-Mei; Gu, Da-Ming; Wang, Zhen-Bo
Abstract : The Pt/NCQDs–MWCNT catalyst shows the best performance for methanol electrooxidation when the precursor content of the NCQDs–MWCNT support is 3 g. Abstract : N-Doped carbon quantum dots (NCQDs)/multiwall-carbon nanotube (MWCNT) supports are synthesized by a one pot hydrothermal treatment process at different contents of precursor. NCQDs–MWCNT as support can be widely used in the process of electrocatalysis. In this paper, the Pt/NCQDs–MWCNT catalysts are prepared by a microwave-assisted polyol process (MAPP) method and the effects of NCQDs with different contents on the performance of Pt-based anode catalysts for methanol oxidation reaction (MOR) are systematically demonstrated. The electrochemical tests reveal that the Pt/NCQDs–MWCNT catalyst exhibits the best performance for MOR when precursor content is 3 g. In terms of the electrochemical and characterization results, the moderate content of precursor for NCQDs plays multiple roles in the electrocatalytic performance: promoting the dispersion of untreated MWCNT significantly in solution; providing the plentiful oxygen-containing groups to deposit Pt nanoparticles; and facilitating the formation of homogeneous Pt nanoparticles.